Improvements in Human Keratinocytes and Antimicrobial Effect Mediated by Cell-Free Supernatants Derived from Probiotics - Ji Yeon Lee; YongGyeong Kim; Ja-I Kim; Hyang-Yeol Lee; Gi-Seong Moon; Chang-Ho Kang (Fermentation, 2022)
The skin acts as a physical and physiological barrier, thereby protecting the body from various environmental components and stimuli. Cell-free supernatants (CFS) derived from probiotics can improve skin functions and retain moisture. In this study, to assess the efficacy of CFS derived from Ligilactobacillus salivarius and Limosilactobacillus fermentum, we investigated the barrier strengthening and moisturizing effects of CFS in keratinocytes along with their antibacterial effects. We also determined the adhesive effects of probiotics on colorectal cells. To confirm improvements in moisturization and barrier function mediated by CFS in keratinocytes, hyaluronic acid (HA) production, and mRNA expression of HA synthases (HAS)2, HAS3, and FLG were measured. The results showed that CFS from L. salivarius MG242 and L. fermentum MG901 increased the expression of these genes along with the production of HA (2.40- and 1.95-fold of control). Additionally, CFS derived from L. salivarius MG242 and L. fermentum MG901 inhibited the growth of S. aureus and E. coli, thereby demonstrating inhibitory effects against harmful pathogens observed on the skin. These results indicate that the use of CFS derived from L. salivarius MG242 and L. fermentum MG901 may increase moisturization in the skin and improve barrier function of keratinocytes along with elimination of potential pathogens.